The Peary caribou (Rangifer pearyi Allen). Bulletin of the AMNH - Allen, J. A. (Joel Asaph), 1838-1921.; Peary, Robert E. (Robert Edwin), 1856-1920. (New York : Published by order of the Trustees, American Museum of Natural History, 1908)
p. 487-504 : ill. 24 cm. Includes bibliographical references.